The effects of facilitated feedback on the second-language English writing of Korean university students - Boggs, J (2018)
Corrective feedback (CF) has been demonstrated in the literature to have a positive effect on language learners’ grammatical accuracy in second-language (L2) writing. However, while much work has been done on feedback type (e.g. direct and indirect CF), studies continue to produce results which seem to contradict each other, indicating that a different focus might be useful. Moreover, much of the work on CF has been conducted with English majors or with participants studying (or preparing to study) in universities in English-speaking settings, but the generalisability of these studies to settings where English is neither the dominant language nor the learners' principal academic focus is unclear. The current study shifts the focus from type of CF to ways of facilitating CF use, exploring the issue with Korean L1 learners of English who are natural science majors at a university in South Korea taking a required English L2 writing course. The current study contributes to the body of knowledge on CF provision by quantitatively and qualitatively investigating how participants’ use of feedback in this context is facilitated by their Western teachers, and how the effects of facilitated feedback use compares to effects in a group whose use of feedback is not facilitated. Working within a cognitive framework of language learning and using a quasi-experimental, mixed-methods, pre-test / post-test / delayed post-test study design, the study explores the differential effects of two ways of facilitating use of CF on the development of grammatical accuracy in written work, which was academic in style. Effects of these two methods of facilitating the use of CF are compared to effects of an unfacilitated condition. The hypothesis that learners would apply explicit knowledge to analyse and address errors in their writing, resulting in increased accuracy in the use of standard forms, is a cognitive one; and the facilitating of the interventions applies concepts from sociocultural theory. Participants in one facilitated condition received CF orally in individual conferences, with the teacher giving contingent assistance and only providing direct CF if needed; participants in the other facilitated condition received direct written CF, and were provided with worksheets designed to structure their independent reflection upon their writing. Finally, the Comparison Group received direct written CF without any facilitation. Measures of the development of accuracy focused on specific grammatical features targeted for instructional and feedback purposes, and assessed improvement in the accuracy in use of those features in new writing. The study applied a process-writing protocol: Write – Receive CF – Revise – Write a new paragraph. Effects of self-efficacy and language aptitude on the effectiveness of the treatments are also considered. Quantitative analyses of the data suggest that providing direct written CF without facilitating its use enabled the development of accuracy equally as well as CF whose use was facilitated, whether by the conferences or the reflective worksheets. Qualitative analyses reveal how teachers facilitated the use of CF in conferences, and how students participated in both forms of facilitation. Findings suggest that previous educational experience may influence learners' ability to effectively use facilitated CF. Finally, interviews with participating teachers and students provide insight into both parties' experiences with these interventions, contributing to knowledge about intervention development and implementation, both in research and in classroom settings.